Innovation and Tradition in Rabbinic Culture : A Reassessment Through a Linguistic Lens - Blankovsky, Yuval, (The Brill Reference Library of Judaism ;, 2020)
Reading Talmudic Sources as Arguments: A New Interpretive Approach elucidates the unique characteristics of Talmudic discourse culture. Approaching Talmudic literature from a linguistic perspective, the book shows the extensive and hidden ways in which later rabbis used early formulations. Applying Quentin Skinner's interpretive question "What was the author doing in composing the text in this particular way?" to Talmudic literature reveals that Talmudic debate is not only about ideas, concepts and laws but also about the latter's connection to pre-existing formulations. These early traditions, rather than only being accepted or not, are used by later generations to build their own arguments. The book articulates the function of tradition at the time that Rabbinic Judaism was forged.